The horizontal stability of an FLNG with different turret locations - Zhi-Tian Xie; Jian-Min Yang; Zhi-Qiang Hu; Wen-Hua Zhao; Jing-Rui Zhao (International Journal of Naval Architecture and Ocean Engineering, 2015)
The horizontal stability of a Single-Point Moored (SPM) Floating Liquefied Natural Gas (FLNG) facility is investigated. Both numerical and experimental studies have been conducted for this SPM FLNG. The numerical simulations feature well the experimental data. The effects of the turret locations are studied based on the validated numerical model. Statistic results of the vessel’s motions with different turret locations are conducted and compared. The results show that the longitudinal location of the turret has a significant influence on the horizontal stability, which has a strong relationship with the yaw and roll motions. The calculated top tensions on the hawsers also develop a regular change as changing the turret’s location. The investigation will provide a brief of principles with more details for the design of the ongoing project.